Synthesis of an ethylenediamine-modified hypercrosslinked polymer and its preliminary study for antipyrine and pamabrom extraction - Subri, Nur Nida Syamimi; Ibrahim, Nur Athirah; Abdullah, Luqman Chuah; Kamaruzaman, Sazlinda; Faujan, Nur Hana; Md. Jamil, Siti Nurul Ain (Malaysian Institute of Chemistry, 2021)
Emerging contaminants (EC) are naturally occurring or synthetic chemicals that may enter the environment and cause adverse effects to aquatic and human health. EC consist of pharmaceuticals, pesticides, organic chemicals and personal care products that present in water sources at low concentrations (μg/L), hence, they are not widely monitored in the environment. Pharmaceuticals contain biologically-active components that pollute water courses. These generally originate from human waste or the uncontrolled release of residues from chemical plants. The removal of pharmaceutical compounds from water can be carried out using polymeric materials with high specific surface areas and good selectivity due to the presence of accessible active functional groups. In the present work, the synthesis and characterizations of microspheres, acrylonitrile-co-divinylbenzene-80-co-vinylbenzylchloride(AN-co-DVB-80-co-VBC) terpolymers with weak-anion-exchange (WAX) character and high porosity have been successfully carried out. The polymeric microspheres were synthesized by precipitation polymerization and subsequently hypercrosslinked (HXL) via a Friedel-Crafts reaction. The HXL terpolymer was then chemically modified with 1,2-ethylenediamine (EDA) to incorporate diamine functional groups, which improved the selectivity of the HXL microspheres towards polar compounds. Fourier Transform-Infrared (FT-IR) spectra of the EDA-modified HXL terpolymer showed that the nitrile groups derived from AN units were utilized due to the presence of diamine groups along the polymeric chains, indicating that the chemical modification was successful. The microanalysis showed that the chlorine content of the polymer was significantly decreased after hypercrosslinking, indicating that the reaction was successful. The nitrogen content increased after chemical modification with EDA, indicating successful chemical modification of the microspheres. The polymers were in the form of spherical monodisperse polymer microspheres with mean particle diameters of ~7.00 μm. The highest observed specific surface areas (SSAs) of the HXL terpolymer and EDA-modified HXL terpolymer were 2,274 m²/g and 503 m²/g, respectively. The microspheres were utilized to extract the pharmaceutical compounds antipyrine and pamabrom from aqueous solution using the dispersive solid phase extraction (DSPE) method. The extraction analysis was carried out by Gas Chromatography–Mass Spectrometry (GC-MS). The influence of adsorbent dosage, extraction time and elution time were studied to evaluate the performance of the adsorbent in the extraction of antipyrine and pamabrom from aqueous solution. It can be concluded that EDA-modified HXL poly(AN-co-DVB-80-co-VBC) was more favourable towards the extraction of antipyrine, which had a maximum extraction efficiency (EE%) of 95%, compared to that of pamabrom (maximum EE% of 54%).